2014
DOI: 10.2196/mhealth.2799
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Lifespace of People With Parkinson’s Disease Using Smartphones: Proof of Principle

Abstract: BackgroundLifespace is a multidimensional construct that describes the geographic area in which a person lives and conducts their activities, and reflects mobility, health, and well-being. Traditionally, it has been measured by asking older people to self-report the length and frequency of trips taken and assistance required. Global Positioning System (GPS) sensors on smartphones have been used to measure Lifespace of older people, but not with people with Parkinson’s disease (PD).ObjectiveThe objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 30 publications
2
59
0
Order By: Relevance
“…Where the study duration was specified, the majority of the studies included in this review described testing of their sensors/technology over two weeks or less, however 10 studies detailed longer period of study time of up to a year [32,34,[41][42][43][44][45][46][47][48]. Data from sensing technology was collected on more than one occasion by three studies.…”
Section: Duration Of Home Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Where the study duration was specified, the majority of the studies included in this review described testing of their sensors/technology over two weeks or less, however 10 studies detailed longer period of study time of up to a year [32,34,[41][42][43][44][45][46][47][48]. Data from sensing technology was collected on more than one occasion by three studies.…”
Section: Duration Of Home Studymentioning
confidence: 99%
“…Given the early nature of this pilot work there was no validation/clinimetric testing documented. The metric of 'lifespace', a phrase given to the number of trips outside a home of > 500 metres, the length of distance travelled and approximate location to which travelled, was measured by Liddle et al [43] using a single Global Positioning System within an Android smartphone. No validation or clinimetric testing was mentioned.…”
Section: Activities Of Daily Livingmentioning
confidence: 99%
“…However, this issue has not been empirically investigated. In addition, the impact of caregiving on family members’ lifespace had received lesser attention in the literature, with most research focussed on the individual's lifespace, such as that of healthy older adults (Schenk et al ., ), and adults with specific health conditions such as Parkinson's disease (Liddle et al ., ), Alzheimer's disease (Tung et al ., ), cognitive impairment (Tsutsumimoto et al ., ), reduced kidney function (Bowling et al ., ) or adults with specific needs such as those who use a wheelchair (Sakakibara, Miller, Eng, Backman & Routhier, ). There is only one study, to the best of our knowledge that reported family members of people with Parkinson's disease had reduced participation in leisure activities, and consequently a reduced lifespace (Lökk, ).…”
Section: Introductionmentioning
confidence: 99%
“…Lifespace is a measure of a person's spatial mobility or the geographical space in which activities are conducted (Schenk et al, 2011). Lifespace has associations with a person's wellbeing and quality of life (Aberg, 2008;Liddle et al, 2014), social interaction (Schenk et al, 2011), level of depression (Polku et al, 2014) and perceived control (Sartori et al, 2012). Studies have demonstrated that a restriction in lifespace affects quality of life as individuals surrender valued roles and reduce their participation in activities (Rantanen, Portegijs, Viljanen & Eronen, 2012;Xue, Fried, Glass, Laffan & Chaves, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Keränen and Liikkanen’s study5 used Short Message Service reminders as a solution to this problem, which showed effective response to adherence among PD patients including complicated cases. In another use of mobile phones, Liddle et al6 used Global Positioning System sensors on smartphones to calculate the Lifespace (geographic area in which a person lives and conducts their activities, and reflects mobility, health and well-being) of PD patients. The idea was to measure the progression and impact of PD among the patients by having an idea of their surroundings.…”
mentioning
confidence: 99%